The Impact of Financial Rewards, Conflict of Management, Promotion, Flexibility of Working Hours, and Working Environment on Employees’ Productivity in Somalia - Mohamud, Hassan Mohamed (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2025)
This study investigated the impact of financial rewards, conflict of management, promotion, flexibility of working hours, and working environment on employees’ productivity. This study employed a quantitative research design to examine the impact of financial rewards, conflict management, promotion opportunities, flexible working hours, and the working environment on employees’ productivity. Data were collected using a structured questionnaire distributed to a sample of 425 respondents, ensuring adequate representation for statistical analysis. The questionnaire was designed to capture both personal profile information and variables related to the study constructs. For the analysis of demographic and personal profile data, the software Jamovi was utilized due to its user-friendly interface and effectiveness in handling descriptive statistics. To assess the relationships among financial rewards, conflict management, promotions, flexible working hours, the working environment, and employee productivity, Structural Equation Modeling (SEM) was conducted using SmartPLS 4. This software was chosen for its suitability in analyzing complex models and measuring correlations among latent variables. The collected data were screened for completeness and accuracy before analysis. Ethical considerations were upheld throughout the study by ensuring respondent confidentiality and voluntary participation. The analysis revealed that financial rewards and flexibility of working hours have a positive effect on productivity. While conflicts of management, promotion and working of environment have a negative impact on employees' productivity.